2007
DOI: 10.1063/1.2760175
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of tapping mode atomic force microscopy in liquids: Theory and experiments

Abstract: A mathematical model is presented to predict the oscillating dynamics of atomic force microscope cantilevers with nanoscale tips tapping on elastic samples in liquid environments. Theoretical simulations and experiments performed in liquids using low stiffness probes on hard and soft samples reveal that, unlike in air, the second flexural mode of the probe is momentarily excited near times of tip-sample contact. The model also predicts closely the tip amplitude and phase of the tip at different set points.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
102
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 105 publications
(106 citation statements)
references
References 16 publications
(23 reference statements)
3
102
0
Order By: Relevance
“…By way of summary, we have shown that the momentary excitation of the second eigenmode is a naturally occurring phenomenon unique to AFM operation using soft cantilevers (k 1 < 1 N=m, Q 1 < 5) in liquids where quality factors are inherently low [10]. This phenomenon is manifest by the enhancement of integer higher harmonics of the drive frequency near the second eigenmode frequency and is quite sensitive to local elasticity when gentle imaging forces (high setpoints) are used.…”
Section: Fig 3 (Color Online)mentioning
confidence: 86%
See 4 more Smart Citations
“…By way of summary, we have shown that the momentary excitation of the second eigenmode is a naturally occurring phenomenon unique to AFM operation using soft cantilevers (k 1 < 1 N=m, Q 1 < 5) in liquids where quality factors are inherently low [10]. This phenomenon is manifest by the enhancement of integer higher harmonics of the drive frequency near the second eigenmode frequency and is quite sensitive to local elasticity when gentle imaging forces (high setpoints) are used.…”
Section: Fig 3 (Color Online)mentioning
confidence: 86%
“…In this Letter, we build on recent work [10] to show that the tapping dynamics of soft AFM cantilevers in liquids features a unique nonlinear transient phenomenon-that of momentary excitation of higher eigenmodes which occurs naturally and does not require higher eigenmode frequencies to be integer multiples of the fundamental. We find these vibrations provide an order of magnitude improvement in compositional contrast on soft biological materials in liquids when compared to second harmonic imaging [5], under gentle imaging conditions and without the use of specialized cantilevers or intentional bimodal excitation [12,14].…”
mentioning
confidence: 99%
See 3 more Smart Citations